A conceptual framework for integrating deltaic food systems and spatial design: the case of the Mekong River Delta - Arbara, Sophia; Hooimeijer, Fransje (Frontiers in Sustainable Food Systems, 2025)
Food and deltaic systems are complex, interlinked systems that are crucial for future sustainable development. This study explores the synergy between these two systems to establish an agroecological framework for delta urbanism. Drawing on political ecology approaches and the infrastructural turn, this study critically revisits food systems to understand how they can be better integrated with hydrological, infrastructural, and urban–rural processes. It also addresses fundamental questions necessary for creating new pathways and redesigning deltaic areas. Second, it examines both past and future models of food equations in relation to the deltaic landscape. Finally, it proposes a spatial framework based on a layered approach that aims to provide an analytical framework for research and design related to deltas and food across various scales and historical timeframes. The operational basis for presenting this methodology is the case of the Mekong River Delta and its rice cultivation territories. Findings emphasize the significance of technological milestones and their spatial implications in shaping resource availability, population growth, and climate change. Further application and operationalization of this framework will provide a deeper understanding of the complex interactions among food production, environmental change, and socioeconomic structures, providing valuable insights into sustainable agricultural practices and climate adaptation.